PENGARUH KEPERCAYAAN, MANFAAT, DAN KEMUDAHAN TERHADAP KEPUTUSAN PENGGUNAANPADA APLIKASI LINKAJA TELKOM JAKARTA - Faisal Fadillah; Hartono Hartono; Dickdick Sodikin (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to determine how much influence the influence of trust, benefits and convenience on the decision to use LinkAja (Case Study on Community Users of LinkAja Services in Jakarta), with quantitativemethods. , each respondent was given 24 questions using a Likert scale and data analysis techniques using validity tests, reliability tests, normality tests and multiple linear regression analysis. To test the hypothesis using the t test, F test and the correlation coefficient test and the coefficient of determination.The results of the hypothesis test show that there is a positive and partially significant (individual) effect between Trust and Usage Decisions. Judging from the calculations that have been made, the coefficient value is 3.264 tcount > ttable 1.668 with a significance level of < (0.05). then there is a positive but not significant effect partially (individually) between the benefits on the decision to use. Judging from the calculations that have been made, the coefficient value is 2.665 tcount > ttable 1.668 with a significance level > (0.05). Then there is a positive and significant influence partially (individually) between Ease of Use Decisions. Judging from the calculations that have been carried out, the coefficient value is 14,138 tcount > ttable 1,668 with a significance level of < (0.05). Then there is a positive and significant effect simultaneously (together) between The Influence of Trust, Benefits and Ease on Usage Decisions. Judging from the calculation, the value (df=N2=n-k) is 3.05, so Fcount > Ftable (758,421>2,68). The influence caused by the independent variable on the dependent variable is 75.4% while the remaining 24.6% is influenced by other factors or variables that were not carried out in this study.Based on this, it is recommended for companies to need application updates for each LinkAJA application service, then the LinkAJA application must be transparent in terms of positive and negative reviews and transparent in terms of providing product availability information in the LinkAJA application, clearly and easily understood by users